Classification Of Accident Proposed Road Data Traffic In Bengkulu City Using K-Means Algorithm - Muhammad Andre Anggara; Anisya Sonita; Muhammad Husni Rifqo; Ardi Wijaya (Jurnal Komputer, Informasi dan Teknologi, 2023)
A traffic accident is an event where a motorized vehicle collides with another object and causes damage. Traffic accident data at the Bengkulu City Police LAKA LANTAS (Traffic Accident) Unit is only used as data reporting where the accident data can actually help to reduce the number of traffic accidents by grouping to facilitate the police in proper handling efforts to reduce the number of traffic accidents. traffic accidents by classifying accident-prone roads. One of the approaches used in developing the clustering method is the K-Means Clustering method, where this method is a data grouping method that attempts to partition data into two or more groups (clusters) with the same characteristics into the same group. The results and discussion of the research obtained a system capable of classifying accident-prone roads using the k-means method. From the tests carried out this system can be used by the POLRESTA in helping these problems.